Two Wnt genes regulate the expression levels of antimicrobial peptides during Vibrio infection in Macrobrachium nipponense. Issue 101 (June 2020) - Wang, Kaiqiang; Dai, Xiaoling; Zhang, Chao; Cao, Xueying; Zhang, Ruidong; Zhang, Zhuoxing; Huang, Xin; Ren, Qian
Abstract: The Wnt signal transduction pathway is involved in a wide variety of cellular processes, including cell proliferation, differentiation, apoptosis, and immunity against microbial infection. In the current study, we cloned and characterized two Wnt homologues ( Mn-Wnt4 and Mn-Wnt16 ) in Macrobrachium nipponense . The full length cDNA of Mn-Wnt4 was 3144 bp with a 1074 bp open reading frame (ORF) that encoded a protein containing 358 amino acid residues. The full length cDNA of Mn-Wnt16 transcript was 2893 bp with a 1281 bp ORF that encoded a 427 amino acid protein. Mn-Wnt4 and Mn-Wnt16 proteins contained a highly conserved WNT1 domain. Tissue distribution analysis showed that Mn-Wnt4 and Mn-Wnt16 were highly expressed in the stomach. The transcriptional levels of Mn-Wnt4 and Mn-Wnt16 in the stomach were upregulated at most tested time points after bacterial ( Staphylococcus aureus and Vibrio parahaemolyticus ) and viral ( White spot syndrome virus ) infection. Moreover, the expression levels of some antimicrobial peptides (AMPs) (including anti-lipopolysaccharide factor [ALF] and crustin [CRU]) were upregulated after V. parahaemolyticus infection. We further used dsRNA-mediated RNA interference technology to explore the relationship between these two Wnt genes and the expression levels of AMPs during V. parahaemolyticus infection. Mn-Wnt4 knockdown could significantly inhibit the expression of ALF1 and CRU4 in the stomach of V. parahaemolyticus -injected prawns, whereas Mn-Wnt16 silencing could result in the inhibition of the expression level of CRU3 and CRU4 in the stomach of V. parahaemolyticus -infected prawns. These findings indicated that the Wnt gene family might participate in the body's innate immune response to Vibrio infection by regulating the synthesis of a variety of AMPs. Our study will help to understand the role of the Wnt signaling pathway in the immune response of crustaceans. Highlights: Two Wnt genes ( Mn-Wnt4 and Mn-Wnt16 ) were identified from Macrobrachium nipponense. Vibrio infection promotes the transcription of Mn-Wnt4, Mn-Wnt16, and some AMPs. Mn-Wnt4 and Mn-Wnt16 knockdown inhibit the expression levels of different AMPs in Vibrio -infected prawns.